[Cp2Mo(OH)(OH2)]+‐Catalyzed Hydrolysis of Mono‐ and Difunctional Ethers: Theoretical Understanding of Their Divergent Reactivity. Issue 24 (12th June 2019) - Álvarez, Daniel; Castro‐López, Elena; Fernández‐Pulido, Yoana; Menéndez, M. Isabel; López, Ramón
Abstract : The reaction mechanism of [Cp2 Mo(OH)(OH2 )] + ‐catalyzed hydrolysis of ethyl vinyl, divinyl, and diethyl ethers was theoretically investigated. The reaction pathway evolving through the coordination of the ether oxygen to Mo is notably disfavored, as experimentally suggested. This is the only operative coordination mode for diethyl ether and explains why this monofunctional ether is not hydrolyzed by molybdocenes. However, difunctional ethers containing a functionality susceptible to activation like the vinyl group present an alternative reaction pathway proceeding through the coordination of the vinyl terminal carbon to Mo with accessible rate‐determining Gibbs energy barriers of 29.3 kcal/mol (divinyl ether) and 22.2 kcal/mol (ethyl vinyl ether). In these cases, the catalyst withdraws electron density from the unsaturated bonds and prepares the group for an easy OH‐nucleophilic attack. This explains the molybdocene‐catalyzed hydrolysis of ethyl vinyl ether experimentally observed and, more interestingly, reveals what the crucial role of the functional groups linked to the ether oxygen really is in the viability of these reactive processes. Abstract : Computations show that the coordination to Mo of ethyl vinyl or divinyl ethers by a terminal vinyl carbon is by far more favorable than routes involving the complexation to ether oxygen or end ethyl carbon. The Mo‐vinyl coordination significantly activates the vinyl carbon directly linked to ether oxygen, thus making easier the nucleophilic attack of the hydroxo ligand.